2021
DOI: 10.1021/acs.jmedchem.1c00847
|View full text |Cite
|
Sign up to set email alerts
|

GDC-9545 (Giredestrant): A Potent and Orally Bioavailable Selective Estrogen Receptor Antagonist and Degrader with an Exceptional Preclinical Profile for ER+ Breast Cancer

Abstract: Breast cancer remains a leading cause of cancer death in women, representing a significant unmet medical need. Here, we disclose our discovery efforts culminating in a clinical candidate, 35 (GDC-9545 or giredestrant). 35 is an efficient and potent selective estrogen receptor degrader (SERD) and a full antagonist, which translates into better antiproliferation activity than known SERDs (1, 6, 7, and 9) across multiple cell lines. Fine-tuning the physiochemical properties enabled once daily oral dosing of 35 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 49 publications
4
107
0
Order By: Relevance
“…It is worth noting that two of the presented molecules, i.e., adavosertib (formerly AZD1775 ) and pemrametostat (formerly GSK3326595 ), are characterized by a completely new mechanism of action, such as WEE1 G2 checkpoint kinase (WEE1) inhibition and protein arginine methyltransferase 5 (PRMT5) inhibition, respectively [ 271 , 272 ]. The next two agents, i.e., ARV-471 and giredestrant (also known as GDC-9545 ) are specifically designed to target and degrade the estrogen receptor (ER) during the treatment of patients with breast cancer [ 273 , 274 ]. It should be emphasized that ARV-471 is one of the first clinically evaluated proteolysis-targeting chimera (PROTAC) molecules.…”
Section: Potential Anticancer Drugs In the Pipelinementioning
confidence: 99%
“…It is worth noting that two of the presented molecules, i.e., adavosertib (formerly AZD1775 ) and pemrametostat (formerly GSK3326595 ), are characterized by a completely new mechanism of action, such as WEE1 G2 checkpoint kinase (WEE1) inhibition and protein arginine methyltransferase 5 (PRMT5) inhibition, respectively [ 271 , 272 ]. The next two agents, i.e., ARV-471 and giredestrant (also known as GDC-9545 ) are specifically designed to target and degrade the estrogen receptor (ER) during the treatment of patients with breast cancer [ 273 , 274 ]. It should be emphasized that ARV-471 is one of the first clinically evaluated proteolysis-targeting chimera (PROTAC) molecules.…”
Section: Potential Anticancer Drugs In the Pipelinementioning
confidence: 99%
“…As mentioned above, fulvestrant is the only approved SERD for the therapy of postmenopausal aBC patients to date. However, since there is a lack of oral bioavailability of fulvestrant, therefore requiring intramuscular injection of it [ 83 , 84 ], other novel SERDs with the potential of oral bioavailability are being investigated [ 85 , 86 , 87 , 88 , 89 ] ( Table 2 ). A first-in-human study on the SERD AZD9496, for instance, showed an acceptable safety profile and a prolongation of disease stabilization in women with hormone-receptor-positive aBC [ 90 ], but its preoperative influence on estrogen receptor expression was not superior to fulvestrant within a recent window of an opportunity trial in eBC [ 91 ].…”
Section: Modern Approaches In Advanced Breast Cancermentioning
confidence: 99%
“…The superior potency was the result of extensive optimization of antagonist and degradation potencies and a relentless focus on achieving the best ligand-lipophilicity efficiency. 3,4 The superior potencies of GDC-9545, coupled with its excellent oral exposure, translate into excellent in vivo efficacies either as a single agent or in combination with a CDK4/6 inhibitor. The projected human efficacious dose is ∼1 mg once per day, targeting tumor regression in the PDX tumor model which harbors an ESR1 mutation.…”
Section: Comparing With Other Oral Serdsmentioning
confidence: 99%
“…The exact reason why a clinical candidate was terminated is often not published. The featured article by Liang et al in this issue of the Journal of Medicinal Chemistry sheds light toward this as the authors disclose their third generation clinical candidate GDC-9545 (giredestrant) …”
Section: The Renaissance Of Oral Serdsmentioning
confidence: 99%